Sustainable local development in relation to complementary currencies on the example of the Polish currency Zielony - Stępnicka, Nina; Sadowska, Beata; Walasek, Robert; Zimon, Grzegorz; Brzozowiec, Dariusz (Technological and Economic Development of Economy, 2023)
The complementary currency Zielony (PLZ) is an example of an economic experiment, operating in Poland since 2015. It is also a new type of economic tool that supports the local economy and influences the creation of sustainable local developments. However, this impact is not direct, as it is realised through a network of micro, small and medium-sized enterprises operating in the local economy, which, among other things, create jobs relevant to the economic prosperity of the region and the life of the local community. The main objective of this article is to demonstrate the relationship between the use of the complementary currency Zielony in Poland by the entities that create the system of this currency and its impact on the economy, in particular on the local sustainable development in the pre-pandemic and pandemic period of Covid-19. The main research problem is formulated in the form of a question: “What are the benefits and opportunities for the economic entities of the local economy as a result of their accession to the complementary currency Zielony system?” The article adopts the following thesis: “The complementary currency Zielony in Poland positively influences the functioning of the local economy and the economic entities that belong to the system and promotes the creation of conditions that are important for sustainable local development. However, it works best when it is not disrupted by administrative barriers and lockdowns, like those that appeared in Poland during the Covid-19 pandemic.” The analysis carried out proved the validity of the thesis and allowed to solve the main problem. The study used the method of critical literature analysis and analysis of statistical data from 2015–2021. First published online 31 January 2023